Pengembangan Aplikasi Augmented Reality “e-Museum” dengan Metode Agile untuk Meningkatkan Pengalaman Pengunjung Museum - Aisha Gemala Jondya; Daffa Pradipta Saputro; Louis Christopher Sungkharisma (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study develops a mobile application with Augmented Reality technology that provides complete information on historical war weapons at the Fatahillah Museum. Information in this application can be displayed properly, structured, and without the risk of being lost or damaged. Application with Augmented Reality technology also allows visitors to have a pleasant experience because each artifact can be seen up close through its 3D model. This can minimize the risk of historical objects being damaged or lost because users do not need to directly touch objects to see up close. Application’s development is carried out using the Agile method and the testing is carried out using the Black Box method. This application runs well with a good level of user satisfaction, where the results of the evaluation are 96,2% satisfied and 3,6% of them were dissatisfied with the application.